ULTRASOUND DIAGNOSIS OF THE MASS IN THE SOFT TISSUES OF THE NECK OF THE CHILD - T. P. Lagunova (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
The article presents a description of the case of a rare abnormality of the thyroid gland in 5 year old girl with a volume lesion of the neck. Ultrasound examination of the patient from surgical unit with referral diagnosis 'a cyst of the neck' identified an accessory lobe of thyroid gland, atypically localized, of the size compared with one of normal thyroid gland. The size of the thyroid gland in typical localization was decreased, levels of thyroid hormones were normal. For the purpose of verification of malformation Doppler effect and color mapping were applied. Diagnose was confirmed by biopsy results.